Heat recovery steam generator technology - Eriksen, Vernon L. (Woodhead Publishing in energy., 2017)
Heat Recovery Steam Generator Technology is the first fully comprehensive resource to provide readers with the fundamental information needed to understand HRSGs. The book's highly experienced editor has selected a number of key technical personnel to contribute to the book, also including burner and emission control device suppliers and qualified practicing engineers. In the introduction, various types of HRSGs are identified and discussed, along with their market share. The fundamental principles of the technology are covered, along with the various components and design specifics that should be considered. Its simple organization makes finding answers quick and easy. The text is fully supported by examples and case studies, and is illustrated by photographs of components and completed power plants to further increase knowledge and understanding of HRSG technology. Presents the fundamental principles and theories behind HRSG technology that is supported by practical design examples and illustrations Includes practical applications of combined cycle power plants and waste recovery that are both fully covered and supported by optimization throughout the book Helps readers do a better job of specifying, procuring, installing, operating, and maintaining HRSGs.